Exploring Dalihan Na Tolu Philosophy in Batak Society towards Disability: Equality, Context, and Inclusion - Sibagariang, Julius Stefanus (The Center for Disability Studies and Services Brawijaya University, 2025)
This artoicle aims to demonstrate the importance of the relationship between philosophy and disability by exploring the perspective of the Dalihan Na Tolu philosophy, which originated from the culture of the Batak society in Indonesia. Batak society emphasizes loyalty and adherence to the deep-rooted and friendly philosophy of Dalihan Na Tolu. This philosophy forms the basis of the Batak society's social relationships, helping to determine social status, function, and attitude. Although Dalihan Na Tolu philosophy has been widely used as a guideline in social interactions, there has been minimal attention to its relevance in disability. Through qualitative research methods with a literature approach, this essay reveals that the Dalihan Na Tolu philosophy can raise awareness of people with disabilities by emphasizing the importance of equality, contextualization, and inclusiveness implemented through respect, love, and support. This essay emphasizes the need to integrate the Dalihan Na Tolu philosophy towards persons with disabilities as a framework for understanding and promoting the rights and well-being of individuals with disabilities. The results of this essay can contribute to creating a more equal, contextual, and inclusive environment for all society, especially for those with disabilities.